HUBUNGAN ANTARA PENGETAHUAN LINGKUNGAN, STATUS SOSIAL EKONOMI DENGAN PERILAKU HIDUP SEHAT - Sri Yamti Runtuni (Jurnal Spatial Wahana Komunikasi dan Informasi Geografi, 2014)
ABSTRACT The research is in purpose to obtain the description and information about environmental science, social-economy status with heathy attitude lifestyle. This research uses two independent variables that is environmental science and social-economy status, and one dependent variables that is heathy attitude lifestyle. Methodeâ€™s application is survey methode. This research has been held in Subdistrict Pasar Rebo East Jakarta on Novembre until Decembre 2011. The researchâ€™s sample is PKK (Housewifes Community) members team of working group (POKJA) as much as 70 persons. Analisys results showed, first: there is a positive relation between environmental science (X1) with healthy attitude lifestyle (Y). As being indicated by correlation coefficient (r) 0,558 and simple linear regression Ã= 88,45 + 1,49 X and determination coefficient (r2) 0,3114, second: there is a positive relation between social-economy status (X2 ) with heathy attitude lifestyle (Y), As being indicated by correlation coefficient (r) 3,46 with simple linear regression Ã = 93,76 + 3,46 X2; Third: there is a positive relation between environmental science and social-economy together with heathy attitude lifestyle, as being indicated by double correlation coefficient (R) 0,450, with determination coefficient R2 0,450 and with double linear regression Ã = 82,38 + 0,98 X2 + 2,47 X2. This researchâ€™s results put up implication that environmental science and social-economy status are two variables which gave a contribution to PKK (Housewifes Community) memberâ€™s heathy attitude lifestyle in subditrict Pasar Rebo East Jakarta. Kata Kunci : Pengetahuan, Sosial, Ekonomi.